MALAYSIAN LICHENS âI I * - GROENHART, P. (REINWARDTIA, 1950)
The Umbilicariaceae are a family of Lichens occurring almost exclusively in temperate regions and moreover frequently growing on rocks. Nevertheless this family is represented in the tropics; it has been reportedfrom tropical America and Africa. As far as data are available they occur on rocks in the upper regions of high mountain-ranges, viz. of the Andes of Bolivia and Peru and of Pico dOrizaba in Mexico from 10,000 feet upwards. For Africa the data are in accordance: Mount Deschen in Abyssinia (14,200 feet) and Mount Kilimanjaro in Kenya (12,000 feet). For the tropics of Asia an early record exists of the appearance of a species of Umbilicaria; until today, however, this indication has not yet been confirmed and as far as I could gather, it has remained the only one. In Zollingers "Systematisches Verzeichniss der im indischen Archi- pel gesammelten Pflanzen," page 8, 1854, one reads: "Ad rupes summi M. Ardjuno (11,000) occurrit Umbilicariae spec, sed nunc in herbario caret." In Moritzis "Systematisches Verzeichniss der von H. Zollinger in den Jahren 1842Ã¢â¬â1844 auf Java gesammelten Pflanzen," 1845-1846, Umbilicaria is not mentioned, although Zollinger climbed Mount Ardjuno in 1844 and the material was collected probably in that year. Later workers on Zollingers lichens did not describe an Umbilicaria from his collections either, so that we may assume it has been lost. On July 20, 1932 and some years later, on March 27, 1937, I ascended the summit of Mount Ardjuno myself and am rather confident that I collected my specimens of Umbilicaria from the same rock as Zollinger did almost a century ago. Up there, just beneath the top at about 3,300 m, there are only a few big rocks on which this species grows. The top itself is 3,339 m. In the somewhat lower surroundings of the top I could not locate any other specimen. On the summits of Mount Welirang (3,156 m), Northern Kembar (3,020 m), Southern Kembar (3,100 m), and Mount Bakal (2,980 m), which all belong to the Mount-Ardjuno complex, I failed to discover Umbilicaria, too. The same holds true for Mount Kawi (Butak;